Dose Comparison of Dexmedetomidine Sedation following Spinal Anesthesia: Parturient versus Nonpregnant Women—A Randomized Trial - Ming Xiong; Biyun Chen; Zurong Hu; Somdatta Gupta; Zhitao Li; Jiping Liu; Jing He; Shivani Patel; Jean Daniel Eloy; Bo Xu (Anesthesiology Research and Practice)
Background. This study was designed to investigate and compare the effective doses of dexmedetomidine for sedation in parturient patients who underwent Cesarean section (CS) and nonpregnant women who underwent elective gynecologic surgery. Methods. The study comprised 60 females aged between 25 and 35. They were divided into two groups. The parturient group received a bolus dose of dexmedetomidine over 15 min after the delivery of the fetus and placenta. In the nonpregnant women group, a bolus of dexmedetomidine was administered intravenously upon the completion of spinal anesthesia. The subsequent dose required by patients in each group was then determined through a modified two-stage Dixon up-and-down sequential method. Probit analysis was used to calculate the ED50 and the ED95 of dexmedetomidine for adequate sedation. Results. The ED50 of dexmedetomidine for adequate sedation in parturient patients was 1.58 μg/kg (1.51–1.66 μg/kg); in nonpregnant women, it was 0.96 μg/kg (0.91–1.01 μg/kg) (95% CI). The ED95 of dexmedetomidine in parturients was 1.80 μg/kg (1.70–2.16) μg/kg and that of nonpregnant women was 1.10 μg/kg (1.04–1.30 μg/kg) (95% CI). The ED50 in parturients was significantly higher than that in nonpregnant women (P<0.05). Conclusion. The ED50 of dexmedetomidine for target sedation in parturients who received spinal anesthesia for CS is greater than 1.5 times that in nonpregnant women who received spinal anesthesia for lower abdominal gynecologic surgery. This study postulates that the dose of dexmedetomidine required to achieve optimal sedation following spinal anesthesia is much higher in parturients than in nonpregnant women undergoing gynecologic surgeries. This trial is registered with NCT02111421.